CURRENT APPROACHES TO THE DESCRIPTION OF SCIENTIFIC ENGLISH - Tofan Dwi Hardjanto (Humaniora, 1991)
In recent years scientific English has received a good deal of attention from researchers working in such diverse fields as Linguistics, ie (Applied) Discourse Analysis and the Sociology of Science. This growing interest in research into scientific English is primarily due to the importance that modern scientific communities have assigned to it. Indeed, over these yearsEnglish seems to have enjoyed dominance over other languages as the language of international publication and it is now becoming more and more prominent in the pu blication of scientific research articles an d papers. Mounting evidence for this English domination has been offered by researchers such as Baldauf & Jernudd (l983a ; 1983b), Swales (1985), and Maher (1986). In 1983, fo r example, Baldauf & Jernudd (l 983a) conducted a study of the language use patterns in the Fisheries literature for 1978. Their analysis of 884 articles indicated that English is the dominant language (amounting to 75%) in the literature they examined. Having established this English domination, they proceeded to the investigation of the relationship between language use and location of writers. They concluded that "the large proportion of English language articles was due mainly to the large number of authors from English speaking countries and by the use of English as a medium of communication by international organizations " (l983a: 254).